KONSEP PENCEGAHAN PAHAM RADIKAL DAN AKSI TEROR DI ERA REVOLUSI INDUSTRI 4.0: TINJAUAN TEORI KOGNISI SOSIAL - Dwi Joko Siswanto; Frangky Silitonga; Shine Pintor Siolemba Patiro (JURNAL MAHATVAVIRYA, 2022)
The purpose of this study is to see how much prevention from radical understanding and acts of terror in the era of the industrial revolution 4.0 by using social cognition theory. In general, social cognition theory is able to understand, explain, and predict the behavior of individuals exposed to radical ideas and acts of terror in the industrial era 4.0. This is because based on the description of the theoretical concept that learning occurs in a social context with dynamic and reciprocal interactions of people, environment, and behavior. A unique feature of this theory is its emphasis on social influence and its emphasis on external and internal social reinforcement. This theory considers the unique ways in which individuals acquire and maintain behavior, while also considering the social environment in which individuals perform behaviors. This theory also takes into account a person's past experience, which is a factor in whether behavioral actions will occur in the future. These past experiences influence reinforcement and expectations, all of which shape whether a person will engage in a particular behavior and the reasons why a person engages in that behavior. In accordance with the theoretical concept, it can be described how someone who is exposed to radicalism and terrorism involves himself, his behavior, and the social environment.